Analysis of Optimal Bidding Strategy of Electric Vehicle Aggregators in Real-Time Energy Market. Issue 4 (March 2021) - Hou, Xiumei; Liu, Wei; Chen, Shiyu; Guo, Yuenan
Abstract: A power price control strategy is proposed for the charging of electric vehicles. Aggregation managers centrally manage the batteries of electric vehicles, and take into account the limited power supply of the grid during peak electricity consumption, and adjust the demand for charging through electricity price control. By analyzing the main body of the smart grid power market, the article constructs a multi-objective economic dispatch model, and uses Matlab to perform numerical simulation experiments on the model to verify the feasibility and effectiveness of the model.